Emission behavior of crumb rubber modified asphalt in the production process. (15th March 2022) - Tang, Naipeng; Zhang, Zhiyu; Dong, Ruikun; Zhu, Hongzhou; Huang, Weidong
Abstract: The volatile and semi-volatile emissions of crumb rubber modified asphalt (CRMA) has a negative effect on atmosphere environment, which might restrict its application in pavement engineering. To solve this problem, it is necessary to understand the emission behavior of CRMA in the production process, which has not been well evaluated yet. The present study aims to investigate the emission behavior of CRMAs during production at 180 °C, 220 °C and 260 °C. Two neat binders and one minus 40 mesh crumb rubber were involved in the preparation of CRMAs. The emission samples were collected by activated charcoal sorbent tube in the laboratory and desorbed by carbon disulfide for further gas chromatography–mass spectrometry (GC-MS) analysis. The results indicate that the emission behavior of volatiles and semi-volatiles can be described with a fast-slow two-stage emission function, consisted of a linear fraction and an exponential fraction. Terminal blend (TB) technology, e.g., 260 °C curing process, offers environmental advantage over traditional wet-process due to the fact that a large amount of emissions in the TB process can be disposed at the refinery. Compared with neat asphalt, crumb rubber modified asphalt (CRMA) has 9 new compounds, including benzothiazole, N-cyclohexylcyclohexanimine, 2, 2, 4-trimethyl-1, 2-dihydroquine, diphenylacetylene, dicyclohexyl disulfide, hexadecanoic acid, octadecanoic acid, N-(1, 3-Dimethylbutyl)-N′-phenyl-1, 4-phenylenediamin, which are mainly derived from accelerators and additives commonly used in the rubber industry. Highlights: Analyze the time dependent emission behavior of typical compounds. Develop a fast-slow two-stage emission function of crumb rubber modified asphalt. Terminal blend (TB) technology offers environmental advantage over traditional wet-process.